Long Non-Coding RNAs: Challenges for Diagnosis and Therapies - Sánchez, Yolanda (Mary Ann Liebert, Inc., 2013)
Long non-coding RNAs (lncRNAs) have emerged as one of the largest and more diverse classes of cellular transcripts. The growing evidence suggests that lncRNAs are key regulatory molecules present at virtually every level of cellular physiology, and their alterations are associated with multiple human diseases. Here we provide a general overview of the known roles of lncRNAs in different diseases, as well as their imminent application as biomarkers and therapeutic targets. We also discuss the challenges and possible strategies for these clinical applications. It is unquestionable that our knowledge of lncRNAs not only adds a new dimension to the molecular architecture of human disease, but also opens up a whole new range of opportunities for treatment.